2022
DOI: 10.3390/ijms23062950
|View full text |Cite
|
Sign up to set email alerts
|

2-Aminoimidazoles Inhibit Mycobacterium abscessus Biofilms in a Zinc-Dependent Manner

Abstract: Biofilm growth is thought to be a significant obstacle to the successful treatment of Mycobacterium abscessus infections. A search for agents capable of inhibiting M. abscessus biofilms led to our interest in 2-aminoimidazoles and related scaffolds, which have proven to display antibiofilm properties against a number of Gram-negative and Gram-positive bacteria, including Mycobacterium tuberculosis and Mycobacterium smegmatis. The screening of a library of 30 compounds led to the identification of a compound, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…There are studies on M. abscessus biofilms and drug activity testing that include multiple isolates, although their primary focus was not on strain variability. These studies showed no major differences between the isolates in terms of drug susceptibility ( Ortíz-Pérez et al, 2011 ; Rodríguez-Sevilla et al, 2018a ; Marini et al, 2019 ; Rodríguez-Sevilla et al, 2019 ; Belardinelli et al, 2022a ; Feizi et al, 2023 ). Nevertheless, it may be worthwhile to further unravel strain-specific biofilm behavior, including antibiotic susceptibility, given the paucity of data on this topic.…”
Section: Culture Condition Complexities—an Overview Of Experimental V...mentioning
confidence: 92%
See 2 more Smart Citations
“…There are studies on M. abscessus biofilms and drug activity testing that include multiple isolates, although their primary focus was not on strain variability. These studies showed no major differences between the isolates in terms of drug susceptibility ( Ortíz-Pérez et al, 2011 ; Rodríguez-Sevilla et al, 2018a ; Marini et al, 2019 ; Rodríguez-Sevilla et al, 2019 ; Belardinelli et al, 2022a ; Feizi et al, 2023 ). Nevertheless, it may be worthwhile to further unravel strain-specific biofilm behavior, including antibiotic susceptibility, given the paucity of data on this topic.…”
Section: Culture Condition Complexities—an Overview Of Experimental V...mentioning
confidence: 92%
“…In addition, essential oils derived from Cymbopogon Flexuos species and the essential oil constituent carvacrol reduced biofilm biomass of developing as well as pre-established biofilms ( Rossi et al, 2017 ; Marini et al, 2019 ). The aminoimidazole AB-2–29, several sulfonamides complexed with metals, and several inhibitors of the dormancy survival regulon DosRS (which is essential for M. abscessus to persist under hypoxic conditions) inhibited biofilm biomass during biofilm development, but did not reduce the biomass of pre-established biofilms ( Bonez et al, 2021 ; Belardinelli et al, 2022a , b ). Moreover, multiple 2-aminoimidazoles, the antibacterial protein RP557, Panax quinquefolius , Coptic chinensis and its main constituent berberine were able to inhibit biofilm development in terms of biomass, yet their activity on pre-established biofilms was not assessed ( Tseng et al, 2020 ; Li et al, 2022 ; Belardinelli et al, 2022a ; He et al, 2023 ).…”
Section: Integrating Biofilm Techniques: Targeting the Myco...mentioning
confidence: 99%
See 1 more Smart Citation
“…Only the AB-2-29 compound showed antibiofilm activity against this pathogen with an IC50 (concentration required to inhibit 50% of biofilm formation) in the range of 12.5 to 25 μM. Curiously, the activity of AB-2-29 was enhanced by the addition of Zn to the culture medium [ 67 ].…”
Section: Antibiofilmmentioning
confidence: 99%